2019
DOI: 10.1111/apa.15019
|View full text |Cite
|
Sign up to set email alerts
|

Norwegian children and adolescents in blended families are at risk of larger one‐year BMI increments

Abstract: Aim To study how sociodemographic factors and family structure associate with baseline BMI z‐scores (BMIz) and BMIz change in 767 Norwegian children aged 6‐15 years. Methods Baseline BMIz and 1‐year BMIz increments in children from the Bergen Growth Study were analysed with linear and logistic regression, according to sociodemographic factors and family structure. A blended family was defined as including a step‐parent and/or half‐sibling. Results In a fully adjusted regression model, baseline BMIz were only s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
2
1
0
Order By: Relevance
“…Overall, the findings of this study are in line with previous cross‐sectional and longitudinal research that observed a higher risk of overweight and a higher BMI in children from single‐parent families 6,9–11 and other non‐traditional families 6,12 . Along with earlier IDEFICS studies 5,6 and a recent systematic review, 34 we showed that living with siblings was associated with a lower BMI z ‐score.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Overall, the findings of this study are in line with previous cross‐sectional and longitudinal research that observed a higher risk of overweight and a higher BMI in children from single‐parent families 6,9–11 and other non‐traditional families 6,12 . Along with earlier IDEFICS studies 5,6 and a recent systematic review, 34 we showed that living with siblings was associated with a lower BMI z ‐score.…”
Section: Discussionsupporting
confidence: 91%
“…Overall, the findings of this study are in line with previous cross‐sectional and longitudinal research that observed a higher risk of overweight and a higher BMI in children from single‐parent families 6 , 9 , 10 , 11 and other non‐traditional families. 6 , 12 Along with earlier IDEFICS studies 5 , 6 and a recent systematic review, 34 we showed that living with siblings was associated with a lower BMI z ‐score. Our study extends the current state of research by indicating that family structure is associated with the MetS which is, however, explained by the association with the BMI.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation